Anomalies in natural populations of amphibians: Methodology for field studies - Ohler, A; Dubois, A (KnE Life Sciences, 2018)
To be really efficient and conclusive, studies on the anomalies in natural populations of amphibians must be carried out in a perspective clearly centered on this topic rather than being a side product of works dealing with other questions. Recommendations are offered here on the methodology for such studies.